A butterfly‐based direct solver using hierarchical LU factorization for Poggio‐Miller‐Chang‐Harrington‐Wu‐Tsai equations. Issue 6 (24th April 2018) - Guo, Han; Liu, Yang; Hu, Jun; Michielssen, Eric
Abstract: A butterfly‐based hierarchical LU factorization scheme for solving the PMCHWT equations for analyzing scattering from homogenous dielectric objects is presented. The proposed solver judiciously re‐orders the discretized integral operator and butterfly‐compresses blocks in the operator and its LU factors. The observed memory and CPU complexities scale as O ( N log 2 N ) and O ( N 1.5 log N ), respectively. The proposed solver is applied to the analyses of scattering several large‐scale dielectric objects.